2014
DOI: 10.7453/gahmj.2014.043
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Therapies for Low Back Pain that Include Complementary and Alternative Medicine Care: A Systematic Review

Abstract: Study Design:Systematic review of the literature.Objective:To evaluate whether an integrated approach that includes different Complementary and Alternative Medicine (CAM) therapies combined or CAM therapies combined with conventional medical care is more effective for the management of low back pain (LBP) than single modalities alone.Summary of Background Data:LBP is one of the leading causes of disability worldwide, yet its optimal management is still unresolved.Methods:The PRISMA Statement guidelines were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 69 publications
0
5
0
6
Order By: Relevance
“…manipulation and massage) and active therapies such as patient-directed exercise, stretching, and core-stability techniques. There is some evidence for such therapies working in the short to medium term 88, 133 . Clearly, they do not work for every patient and there are a host of factors that influence their efficacy above and beyond the pain mechanism – e.g.…”
Section: Pain Mechanisms (Table 2)mentioning
confidence: 99%
“…manipulation and massage) and active therapies such as patient-directed exercise, stretching, and core-stability techniques. There is some evidence for such therapies working in the short to medium term 88, 133 . Clearly, they do not work for every patient and there are a host of factors that influence their efficacy above and beyond the pain mechanism – e.g.…”
Section: Pain Mechanisms (Table 2)mentioning
confidence: 99%
“…In general, doing exercises is considered as a common treatment method for back pains with no specific causes. Various studies showed that exercise therapy effectively improved chronic back pain, and no negative reports indicate the negative effects of exercise during pregnancy (11,12). Furthermore, some studies demonstrated that the females who regularly exercised during pregnancy had shorter active phase of delivery, lower cesarean rate, lower meconium-stained amniotic fluid, lower fetal distress, fresher mood and could tolerate labor pain more easily (13).…”
Section: Introductionmentioning
confidence: 99%
“…The number of respondents using acupuncture in 2013 was significantly higher than in 1999 and, although official data do not exist, this could be because of the establishment of the Chinese Medical Practitioners Register in Hong Kong in 2002, which has allowed those seeking treatment to be reassured of the legitimacy of the practitioner. A search of the medical literature shows that acupuncture for pain relief, from chronic back pain to labor pain, is becoming more and more popular in Western countries . There are no data on how often acupuncture practices for chronic pain are employed in Western countries and, although efficacy is controversial, a few studies have found acupuncture to be effective …”
Section: Discussionmentioning
confidence: 99%